1993
DOI: 10.2307/3869719
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Carotenoid Biosynthesis during Tomato Development

Abstract: Phytoene synthase (Psy) and phytoene desaturase (Pds) are the first dedicated enzymes of the plant carotenoid biosynthesis pathway. We report here the organ-specific and temporal expression of PDS and PSY in tomato plants. Light increases the carotenoid content of seedlings but has little effect on PDS and PSY expression. Expression of both genes is induced in seedlings of the phytoene-accumulating mutant ghost and in wild-type seedlings treated with the Pds inhibitor norflurazon. Roots, which contain the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 12 publications
5
65
0
3
Order By: Relevance
“…To be sure, the mRNA level is upregulated in flowers relative to leaves, but it remains very low during flower development. A surprisingly small increase for phytoene desaturase transcripts has also been determined in ripening tomato fruit, using RT-PCR (Giuliano et aL, 1993). The level of the transcript coding for the 23 kDa OEC subunit is much higher.…”
Section: Discussionmentioning
confidence: 93%
“…To be sure, the mRNA level is upregulated in flowers relative to leaves, but it remains very low during flower development. A surprisingly small increase for phytoene desaturase transcripts has also been determined in ripening tomato fruit, using RT-PCR (Giuliano et aL, 1993). The level of the transcript coding for the 23 kDa OEC subunit is much higher.…”
Section: Discussionmentioning
confidence: 93%
“…First-strand cDNA synthesis was performed in a 20-µL-reaction volume consisting of 3 µg of total RNA, oligodT [12][13][14][15][16][17][18] and SuperScript TM reverse transcriptase (GIBCO BRL). The reaction was allowed to proceed at 42 ºC for 50 min before being terminated by treatment at 70 ºC for 15 min.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…However, mutations in the gene encoding the phytoene desaturase itself (designated PDS3) [14] have not been reported. Expression analysis of the gene (PDS3) encoding the phytoene desaturase indicated that it is highly regulated by light [18,19] in tomato. Nevertheless, analysis of the immutans mutant showed that the expression of PDS3 gene was not necessarily correlated to the amount of pigments in the cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the case of LHA2 amplification a number of PCR products were cloned and sequenced and a11 corresponded to LHA2. Each competitive PCR experiment produced only two products of the size corresponding to the target and competitor RNA species and quantification of these products was by the method of Guiliano et al (1993). Products were separated by electrophoresis on a 1.5% agarose gel containing 0.2 mg/ mL ethidium and photographed (Polaroid type 55 film), and the intensity of the bands was quantified by scanning the negative on the BioImage analysis system (Millipore).…”
Section: Quantification Of Mrna By Competitive Pcrmentioning
confidence: 99%